INTEGRATION OF PROJECT BASED LEARNING (PjBL) AND PICTURE AND PICTURE (PaP) LEARNING MODELS ON PROCESS SKILLS, CRITICAL THINKING AND LEARNING OUTCOMES OF CLASS X IPA STUDENTS AT SMA MUHAMADIYAH MASOHI AND SMA NEGERI 15 CENTRAL MALUKU - Tuanany, Nahriah; Wael, Syahran; Tuaputty, Hasan (Universitas Pattimura, 2023)
Project based learning (PjBL) is a learning model that uses problems as a first step in collecting and integrating new knowledge based on real experience, Picture and picture (PaP) is a model using media in the form of images so that students are more focused and learning conditions pleasant. Integration between these two learning models to complement each other's strengths and cover each other's weaknesses so that what is expected after the learning process can be achieved, Integration of project based learning (PjBL) and Picture and Picture (PaP) learning models as independent variables, process skills, critical thinking and learning outcomes as the dependent variable. The aim of the study was to determine the effect of the integration of Project Based Learning (PjBL) and Picture and Picture (PaP) learning models on the ability of processing skills, critical thinking and learning outcomes of class X IPA SMA Muhamadiyah Masohi and SMA Negeri 15 Maluku Tengah. The research method is Quasi Experiment with 2 control classes (lecture method), 2 experimental classes (PjBL & PaP integration). The results showed that there was an increase in learning outcomes (87.08), process skills (85.14) critical thinking (84.20) students of class X IPA SMAN 15 Maluku Tengah, increased learning outcomes (83.10), process skills (83 .93), critical thinking (80.00) class X IPA SMA Muhamadiyah Masohi. The LSD test shows that there is an effect of integration of PjBL & PaP on process skills with critical thinking (0.020) Class X IPA 2 SMA Muhamadiyah Masohi, there is an effect of integration of PjBL & PaP on process skills with learning outcomes (0.014), and on learning outcomes with critical thinking (0.030). The conclusion is that there is an influence of the integration of Project Based Learning (PjBL) and Picture and Picture (PaP) learning models on the ability of processing skills, critical thinking and learning outcomes of class X IPA SMA Muhamadiyah Masohi and SMA Negeri 15 Maluku Tengah.